Doped lithium aluminum titanium phosphate solid electrolyte material, preparation method thereof and lithium ion battery containing doped lithium aluminum titanium phosphate solid electrolyte material

By adding doped elements and aluminum fluoride to the titanium aluminum phosphate material, doped titanium aluminum phosphate is prepared by high-temperature solid phase method, which solves the low conductivity and density of the material and achieves high-efficiency lithium ion conductivity and particle density increase, suitable for industrial production.

CN119275333AActive Publication Date: 2025-01-07CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411413379.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-07
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

At this stage, the low ionic conductivity, low particle density and increased impurity phase of titanium aluminum lithium phosphate solid electrolyte materials have limited their application in lithium-ion batteries.

Method used

By adding doped elements to the raw materials containing doped elements to the titanium aluminum phosphate material, doped titanium aluminum phosphate is prepared by high-temperature solid phase method, including aluminum fluoride as flux, and then crushing, crushing and ultrafine ball milling after calcination and synthesis. Form solid electrolyte materials with high conductivity and high particle density.

Benefits of technology

It improves lithium ion conductivity and particle density, solves the problem of low ion conductivity and density of the material, is suitable for industrial scale production, and inhibits the formation of impurity phases, improving the purity and performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275333A_ABST
    Figure CN119275333A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery electrode materials, in particular to a doped lithium aluminum titanium phosphate solid electrolyte material, a preparation method and a lithium ion battery containing the doped lithium aluminum titanium phosphate solid electrolyte material. The chemical composition of the doped solid electrolyte material is Li1 + zMyAlxTi2-x-yP3O12-bFa, wherein x is greater than or equal to 0 and less than or equal to 0.4, a is greater than or equal to 0 and less than or equal to 0.8, and b is greater than or equal to 0 and less than or equal to 0.8. Z is less than or equal to 0.8, and M is one or more of Zn, Mg, Ca, Sr, Si and Sn. Raw materials containing doping elements are added in the process of preparing lithium titanium aluminum phosphate (LATP), doping type lithium titanium aluminum phosphate is synthesized through calcination, then crushing and smashing are conducted, and the solid electrolyte material with high conductivity and particle density is obtained. According to the solid electrolyte material, the ionic conductivity and the particle density are improved, and the requirements of the market for high ionic conductivity and high particle density are met; the preparation method and modification steps are simple, the period is short, and the method is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery electrode materials, and in particular to a doped lithium aluminum titanium phosphate solid electrolyte material, a preparation method and a lithium ion battery containing the same. Background Art

[0002] At present, with the continuous use of traditional fossil energy, it is inevitable that environmental pollution has been brought about, leading to the gradual destruction of the earth's ecological environment. The development of efficient and environmentally friendly green energy has become a general trend. Lithium-ion batteries (LIBs) have been widely developed and applied due to their high energy density and green environmental protection.

[0003] At present, although liquid lithium-ion batteries have been used on a large scale, traditional organic electrolyte lithium-ion batteries have flammable and explosive safety hazards. Among them, lithium aluminum titanium phosphate (LATP) oxide solid electrolyte has been studied intensively due to its safety and green characteristics, but it still has problems such as low ion conductivity and low particle density that limit its development. In order to make up for the defects of lithium aluminum titanium phosphate solid electrolyte materials themselves, researchers have provided many improvement plans to solve such problems. At this stage, doping with lithium aluminum titanium phosphate solid electrolyte materials is the most commonly used improvement method. Doping with elements can make the crystal structure denser and increase lithium ion transmission channels, thereby improving the ionic conductivity of the material. In addition, element doping can also stabilize the crystal structure and inhibit Ti 4+ The reduction of ions reduces side reactions, thereby contributing to the uniform deposition of lithium, inhibiting dendrite formation and preventing the battery from short-circuiting during cycling.

[0004] However, there are still many defects in the doping of lithium aluminum titanium phosphate materials at this stage. The silicon-doped lithium aluminum titanium phosphate material prepared by the molten salt method has low ionic conductivity; the tin-doped lithium aluminum titanium phosphate material has low particle density; the high ionic conductivity silicon-doped lithium aluminum titanium phosphate material prepared by the solution method and subsequent sintering, as the sintering temperature increases, the impurity phase in the material gradually increases.

[0005] Therefore, how to provide a new type of doped lithium aluminum titanium phosphate solid electrolyte material with high ionic conductivity and particle density is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0006] In view of this, the present invention aims to solve the problems of low ion conductivity, low particle density and increased impurity phase of current materials and provides a doped lithium aluminum titanium phosphate solid electrolyte material, a preparation method and a lithium ion battery containing the same.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The first technical objective of the present invention is to provide a doped lithium titanium aluminum phosphate solid electrolyte material, characterized in that the chemical composition of the doped lithium titanium aluminum phosphate solid electrolyte material is Li 1+z M y Al x Ti 2-x-y P3O 12-b F a ; wherein,

[0009] 0 ≤ x, y ≤ 0.4, 0 ≤ a, b ≤ 0.8, 0 < z ≤ 0.8, and M is one or a combination of more than one of the elements Zn, Mg, Ca, Sr, Si, and Sn.

[0010] The second technical objective of the present invention is to provide a preparation method of the doped lithium titanium aluminum phosphate solid electrolyte material as described above.

[0011] A preparation method of a doped lithium titanium aluminum phosphate solid electrolyte material specifically includes the following steps:

[0012] (1) Mix an excessive lithium source and aluminum source, titanium source, phosphorus source, fluorine source, and a compound containing a doping element weighed according to the stoichiometric ratio. Weigh zirconia balls and add the mixed raw materials into a ball milling tank, add an appropriate amount of solvent to submerge the raw materials, then carry out wet ball milling, and then obtain uniformly mixed raw materials through drying and screening;

[0013] (2) Pelletize the uniformly mixed raw materials obtained in step (1) to obtain a dense precursor;

[0014] (3) Transfer the uniformly mixed raw materials obtained in step (1) or the dense precursor after pelletizing in step (2) to a corundum crucible for calcination to obtain an intermediate;

[0015] (4) Crush, wet ball mill, dry, and screen the intermediate obtained in step (3) to obtain an intermediate powder;

[0016] (5) Pelletize the intermediate powder obtained in step (4) to obtain a dense intermediate;

[0017] (6) Calcinate the intermediate obtained in step (3), the intermediate powder obtained in step (4), or the dense intermediate obtained in step (5) again, and cool to room temperature to obtain the doped lithium titanium aluminum phosphate solid electrolyte material.

[0018] Optionally, the method further includes: crushing and pulverizing the intermediate obtained in step (3) or the doped lithium titanium aluminum phosphate solid electrolyte material obtained in step (6), carrying out ultra-fine ball milling, and then drying and screening to obtain an ultra-fine doped lithium titanium aluminum phosphate solid electrolyte material.

[0019] Furthermore, the particle size of the ultrafine doped lithium titanium aluminum phosphate solid electrolyte material is 0.02 to 2 microns.

[0020] Optionally, in step (1), the fluorine source is one or more combinations of aluminum fluoride, magnesium fluoride, calcium fluoride, zinc fluoride, tin fluoride, zirconium fluoride, silicon fluoride, and lithium fluoride, the molar ratio of the lithium source is 10%-20% excess, and the solvent is one or more combinations of water or alcohol solvents, preferably water, alcohol, and isopropanol.

[0021] Optionally, the calcination process parameters in step (3) are: heating to 400-600°C at a heating rate of 1-10°C / min and keeping warm for 2-4h, then heating to 800-1000°C at a heating rate of 1-5°C / min and keeping warm for 2 to 12 hours.

[0022] Optionally, in step (2) and step (5), the briquetting pressure is 5-30 MPa and the briquetting time is 3-30 min.

[0023] Optionally, the temperature of the re-calcination in step (6) is 800-1200° C., and the insulation time is 2 to 12 hours.

[0024] The third technical purpose of the present invention is to provide a lithium-ion battery, which includes the doped lithium aluminum titanium phosphate solid electrolyte material as described above or the doped lithium aluminum titanium phosphate solid electrolyte material prepared by the method as described above.

[0025] It can be seen from the above technical solutions that, compared with the prior art, the doped lithium aluminum titanium phosphate solid electrolyte material, preparation method and lithium ion battery containing the same provided by the present invention have the following excellent effects:

[0026] 1. The present invention adds raw materials containing doping elements during the preparation of lithium titanium aluminum phosphate (LATP), calcines and synthesizes doped lithium titanium aluminum phosphate, and then crushes, pulverizes, and ultrafinely ball-mills the above materials to obtain ultrafine doped lithium titanium aluminum phosphate solid electrolyte materials. From the perspective of the preparation method, the high-temperature solid phase method is suitable for industrial large-scale production, has simple doping steps and a short cycle, and solves the problems of low ion conductivity, low particle density, and low purity (forming impurity phase) of lithium titanium aluminum phosphate (LATP) at this stage.

[0027] 2. In the doped lithium titanium aluminum phosphate solid electrolyte material disclosed in the present invention, aluminum fluoride in the raw material serves as a flux to reduce the sintering temperature and energy consumption; fluorine is doped into the lattice oxygen sites of the lithium titanium aluminum phosphate material to reduce the lattice spacing and form defects in the lattice, which is helpful to form lithium ion diffusion channels; the addition of fluorine promotes the growth of grains, thereby increasing the particle density of the lithium titanium aluminum phosphate electrolyte; fluorine doping can also inhibit the formation of the impurity phase LiTiPO5 to a certain extent, thereby increasing the purity of the lithium titanium aluminum phosphate electrolyte, which is beneficial to improving the ion transport performance and particle density of the lithium titanium aluminum phosphate solid electrolyte.

[0028] 3. The doped lithium aluminum titanium phosphate solid electrolyte material disclosed in the present invention makes the unstable Ti 4+ The ion part is replaced by metal cations with large ionic radius and high electronegativity (Zn 2+ Mg 2+ , Ca 2+ , Sr 2+ 、Si 4+ Sn 4+ ) replacement makes the crystal structure dense and improves the ionic conductivity of the solid electrolyte.

[0029] In summary, the present invention adds raw materials containing doping elements during the preparation of lithium titanium aluminum phosphate, calcining and synthesizing doped lithium titanium aluminum phosphate, and then crushing and pulverizing to obtain a solid electrolyte material with high conductivity and particle density. The solid electrolyte material improves ion conductivity and particle density, meeting the market demand for high ion conductivity and high particle density; and the preparation method and modification steps are simple, the cycle is short, and it is suitable for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0031] Figure 1 This is a SEM image of the fluorine-doped intermediate in Example 1 of the present invention.

[0032] Figure 2 This is a SEM image of fluorine-doped lithium aluminum titanium phosphate in Example 1 of the present invention.

[0033] Figure 3 This is the XRD spectrum of fluorine-doped lithium aluminum titanium phosphate in Example 1 of the present invention.

[0034] Figure 4 This is the XRD spectrum of lithium aluminum titanium phosphate in Comparative Example 2 of the present invention.

[0035] Figure 5 This is the AC impedance diagram of fluorine-doped lithium aluminum titanium phosphate in Example 1 of the present invention.

[0036] Figure 6 This is the AC impedance diagram of lithium aluminum titanium phosphate in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The embodiment of the present invention discloses a doped lithium aluminum titanium phosphate solid electrolyte material, a preparation method and a lithium ion battery containing the same.

[0039] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0040] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0041] Example 1

[0042] 3.25g of lithium hydroxide monohydrate, 0.09g of aluminum oxide, 7.04g of titanium dioxide, 17.9g of ammonium dihydrogen phosphate and 1.16g of aluminum fluoride were mixed with anhydrous ethanol, and 150g of zirconium oxide balls were added, and ball milled at 300rpm for 5h. Then, it was dried at 80℃ for 5h and sieved to obtain a uniformly mixed precursor. The above precursor was placed in a corundum crucible, heated to 500℃ at a rate of 5℃ / min and kept warm for 2h, and then continued to heat to 800℃ and kept warm for 8h to obtain an intermediate. The above intermediate was crushed, ball milled, dried and sieved to obtain an intermediate powder. The above powder was kept at a pressure of 10MPa for 10min to obtain a dense intermediate, and then heated to 800℃ at a rate of 5℃ / min and kept warm for 8h to obtain a fluorine-doped lithium aluminum titanium phosphate material. The above materials were crushed, mixed with anhydrous ethanol, and milled with zirconium oxide balls at 300 rpm for 5 hours, followed by drying at 80° C. for 5 hours and sieving to obtain fluorine-doped ultrafine lithium titanium aluminum phosphate solid electrolyte material.

[0043] The room temperature ionic conductivity of the above materials reaches 1.0*10 -3S / cm, and the particle density reaches 95%.

[0044] Example 2

[0045] 8.14g of lithium hydroxide monohydrate, 0.66g of alumina, 17.6g of titanium dioxide, 44.8g of ammonium dihydrogen phosphate, 2.18g of aluminum fluoride were mixed with anhydrous ethanol, and 370g of zirconium oxide balls were added, and ball milled at 400rpm for 4h. Then, it was dried at 100℃ for 4h and sieved to obtain a uniform precursor powder. The above powder was kept at a pressure of 15MPa for 4min to obtain a dense precursor. The above precursor was placed in a corundum crucible, and then pre-burned at 400℃, kept warm for 4h, and sintered at 850℃ and kept warm for 12h to obtain an intermediate. Subsequently, the above intermediate was crushed, ball milled, dried, and sieved, and sintered at 850℃ and kept warm for 12h to obtain a fluorine-doped lithium titanium aluminum phosphate material. The heating rate of the above steps was 3℃ / min. Subsequently, the above material was crushed, ball milled, dried, and sieved to obtain a fluorine-doped ultrafine lithium titanium aluminum phosphate solid electrolyte material.

[0046] Example 3

[0047] 16.3g of lithium hydroxide monohydrate, 2.2g of alumina, 35.3g of titanium dioxide, 89.7g of ammonium dihydrogen phosphate, 2.91g of aluminum fluoride were mixed with deionized water, and 730g of zirconium oxide balls were added, and ball milled at 500rpm for 3h. Then, it was dried at 120℃ for 3h and sieved to obtain a uniform precursor powder. The above powder was kept at a pressure of 20MPa for 3min to obtain a dense precursor. Then, the above precursor was placed in a corundum crucible, pre-burned at 600℃, kept warm for 4h, sintered at 900℃ and kept warm for 8h to obtain an intermediate. The above intermediate was crushed, ball-milled, dried, sieved, and the powder was pressed into a block to obtain a dense intermediate, sintered at 900℃ and kept warm for 8h to obtain a fluorine-doped lithium titanium aluminum phosphate material, and the heating rate of the above steps was 10℃ / min. Subsequently, the above materials are crushed, ball-milled, dried and sieved to obtain fluorine-doped ultrafine lithium titanium aluminum phosphate solid electrolyte material.

[0048] Example 4

[0049] 81.7g of lithium hydroxide monohydrate, 15.5g of aluminum oxide, 176.8g of titanium dioxide, 449.3g of ammonium dihydrogen phosphate and 7.3g of aluminum fluoride were mixed with deionized water, and 3700g of zirconium oxide balls were added, and ball milling, drying and sieving were performed to obtain a uniformly mixed precursor raw material. The ball milling and drying parameters of this embodiment are the same as those of Example 1. The above precursor was placed in a corundum crucible, and then pre-burned at 500°C, kept warm for 4h, and then sintered at 1000°C and kept warm for 12h to obtain an intermediate. The above intermediate was crushed, ball milled, dried, sieved, sintered at 1000°C and kept warm for 12h to obtain a fluorine-doped lithium titanium aluminum phosphate material, and the heating rate of the above steps was 1°C / min. Subsequently, the above material was crushed, ball milled, dried, and sieved to obtain a fluorine-doped ultrafine lithium titanium aluminum phosphate solid electrolyte material.

[0050] Example 5

[0051] 9.32g of lithium hydroxide monohydrate, 0.66g of aluminum oxide, 1.05g of zinc oxide, 16.5g of titanium dioxide, 44.4g of ammonium dihydrogen phosphate and 2.16g of aluminum fluoride were mixed with anhydrous ethanol, and 370g of zirconium oxide balls were added, ball milled, dried and sieved to obtain a uniform precursor, wherein the ball milling and drying parameters were the same as those in Example 2. The above powder was briquette to obtain a dense precursor, and the above briquetting pressure and time were 15MPa and 5min, respectively. The above precursor was placed in a corundum crucible, then pre-burned at 400°C, kept warm for 4h, sintered at 850°C, and kept warm for 12h to obtain an intermediate. Subsequently, the above intermediate was crushed, ball milled, dried, sieved, sintered at 850°C and kept warm for 12h to obtain a lithium titanium aluminum phosphate material co-doped with fluorine and zinc, and the heating rate of the above steps was 3°C / min. Subsequently, the above materials are crushed, ball-milled, dried and sieved to obtain ultrafine lithium titanium aluminum phosphate solid electrolyte material co-doped with fluorine and zinc.

[0052] Example 6

[0053] 21g of lithium hydroxide monohydrate, 1.3g of aluminum oxide, 4.16g of zinc oxide, 30.6g of titanium dioxide, 88.3g of ammonium dihydrogen phosphate and 4.3g of aluminum fluoride were mixed with deionized water, and 750g of zirconium oxide balls were added, and the mixture was ball-milled, dried and sieved to obtain a uniform precursor powder. The ball-milling and drying parameters of this embodiment are the same as those of Example 3 to obtain a uniform precursor powder. The above powder was pressed into blocks to obtain a dense precursor. The above pressing pressure and time were 20MPa and 3min, respectively. The above precursor was placed in a corundum crucible, and then pre-burned at 600°C, kept warm for 4h, heated to 900°C, sintered and kept warm for 8h to obtain an intermediate. The heating rate of this embodiment is 10°C / min. The above intermediate was then crushed, ball-milled, dried and sieved, and the powder was pressed into blocks to obtain a dense intermediate. The dense intermediate is sintered at 900°C and kept warm for 8 hours to obtain a fluorine- and zinc-co-doped lithium titanium aluminum phosphate material. The material is then crushed, ball-milled, dried, and sieved to obtain a fluorine- and zinc-co-doped ultrafine lithium titanium aluminum phosphate solid electrolyte material.

[0054] Example 7

[0055] 110.6g of lithium hydroxide monohydrate, 8.65g of aluminum oxide, 31.1g of zinc oxide, 152.5g of titanium dioxide, 439.3g of ammonium dihydrogen phosphate and 7.13g of aluminum fluoride were mixed with deionized water, and 3750g of zirconium oxide balls were added, and the precursor was ball-milled, dried and sieved to obtain a uniform precursor. The ball-milling and drying parameters of this embodiment were the same as those of Example 3. The above precursor was placed in a corundum crucible, and then the above precursor was pre-burned at 500°C, and after being kept warm for 4 hours, the temperature was continued to be raised to 1000°C and sintered for 12 hours to obtain an intermediate. The heating rate of this embodiment was 3°C / min. The above intermediate was then crushed, ball-milled, dried and sieved, and the above powder was pressed into a compact intermediate. The above pressing pressure and time were 30MPa and 3min, respectively, and the sintering was carried out at 1000°C and kept warm for 12 hours to obtain a lithium aluminum titanium phosphate material co-doped with fluorine and zinc. Subsequently, the above materials are crushed, ball-milled, dried and sieved to obtain ultrafine lithium titanium aluminum phosphate solid electrolyte material co-doped with fluorine and zinc.

[0056] Example 8

[0057] 16.4g of lithium hydroxide monohydrate, 2.22g of aluminum oxide, 35.5g of titanium dioxide, 90.3g of ammonium dihydrogen phosphate, 2.93g of aluminum fluoride and 1.06g of magnesium oxide were mixed with isopropanol, and 750g of zirconium oxide balls were added, and the precursor was ball-milled, dried and sieved to obtain a uniform precursor. The ball-milling and drying parameters of this embodiment are the same as those of Example 1. The above precursor was placed in a corundum crucible, and then the precursor was pre-burned at 600°C, kept warm for 2h, and then continued to heat to 900°C for sintering, and kept warm for 8h to obtain an intermediate. The heating rate of this embodiment is 1°C / min. The above intermediate was sintered at 800°C and kept warm for 8h to obtain a fluorine- and magnesium-doped lithium aluminum titanium phosphate material. The above material was then crushed, ball-milled, dried and sieved to obtain an ultrafine lithium aluminum titanium phosphate solid electrolyte material doped with fluorine and magnesium.

[0058] Example 9

[0059] 16.5g of lithium hydroxide monohydrate, 0.45g of aluminum oxide, 35.6g of titanium dioxide, 90.5g of ammonium dihydrogen phosphate, 5.9g of aluminum fluoride and 2.1g of magnesium oxide were mixed with isopropanol, and 750g of zirconium oxide balls were added, and the mixture was ball-milled, dried and sieved to obtain a uniform precursor powder. The ball-milling and drying parameters of this embodiment are the same as those of Example 2. The above powders were pressed into blocks to obtain a dense precursor. The pressing pressure and time of this embodiment were 10MPa and 10min, respectively. The above precursor was placed in a corundum crucible, and then pre-burned at 500°C. After keeping the temperature for 4h, the temperature was continued to rise to 800°C for sintering, and the temperature was kept for 12h to obtain an intermediate. The heating rate of this embodiment was 3°C / min. The above intermediate was then crushed, ball-milled, dried and sieved, and the above powder was pressed into blocks to obtain a dense intermediate. The dense intermediate is sintered at 900°C and kept warm for 12 hours to obtain a fluorine- and magnesium-doped lithium aluminum titanium phosphate material. The material is crushed, ball-milled, dried, and sieved to obtain a fluorine- and magnesium-doped ultrafine lithium aluminum titanium phosphate solid electrolyte material.

[0060] Example 10

[0061] 10.5g of lithium hydroxide monohydrate, 1.96g of aluminum oxide, 2.09g of zinc oxide, 15.4g of titanium dioxide and 44.3g of ammonium dihydrogen phosphate were mixed with anhydrous ethanol, and 370g of zirconium oxide balls were added, and the mixture was ball-milled, dried and sieved to obtain a uniform precursor. The ball-milling and drying parameters of this embodiment are the same as those of Example 3. The above precursor was placed in a corundum crucible, and then pre-burned at 600°C, kept warm for 2h, and then continued to heat up to 900°C, and kept warm for 8h to obtain an intermediate. The heating rate of this embodiment is 5°C / min. The above intermediate was then crushed, ball-milled, dried, sieved, and pressed into a compact intermediate. The pressure and time of the above pressing step were 20MPa and 3min, respectively. The above compact intermediate was heated to 1000°C and kept warm for 8h to obtain a zinc-doped lithium titanium aluminum phosphate material. The above material was crushed, ball-milled, dried and sieved to obtain a zinc-doped ultrafine lithium titanium aluminum phosphate solid electrolyte material.

[0062] Embodiment 11

[0063] 8.28g of lithium hydroxide monohydrate, 2.0g of aluminum oxide, 17.9g of titanium dioxide, 45.6g of ammonium dihydrogen phosphate and 1.07g of magnesium oxide were mixed with deionized water, and 370g of zirconium oxide balls were added, and ball milling, drying and sieving were performed to obtain a uniform precursor. The ball milling and drying parameters of this embodiment are the same as those of Example 3. The above powders were briquette to obtain a dense precursor. The briquetting pressure and time of this embodiment were 30MPa and 3min, respectively. The above precursor was placed in a corundum crucible, pre-burned at 500°C and kept warm for 4h, and then continued to heat to 900°C for sintering, and kept warm for 12h to obtain an intermediate. The heating rate of this embodiment was 10°C / min. The above materials were crushed, ball milled, dried and sieved to obtain a magnesium-doped ultrafine lithium titanium aluminum phosphate solid electrolyte material.

[0064] Example 12

[0065] 18.8g of lithium hydroxide monohydrate, 4.0g of aluminum oxide, 2.1g of zinc oxide, 1.1g of magnesium oxide, 33.3g of titanium dioxide and 89.8g of ammonium dihydrogen phosphate were mixed with anhydrous ethanol, and 750g of zirconium oxide balls were added, and ball milling, drying and sieving were performed to obtain a uniform precursor. The ball milling and drying parameters of this embodiment are the same as those of Example 1. The above precursor was placed in a corundum crucible, and then pre-burned at 500°C and kept warm for 2h, and then continued to heat to 900°C for sintering, and kept warm for 8h to obtain an intermediate. The heating rate of this embodiment is 5°C / min. The above materials were crushed, ball milled, dried and sieved to obtain an ultrafine lithium titanium aluminum phosphate solid electrolyte material co-doped with zinc and magnesium.

[0066] Comparative Example 1

[0067] 8.18g of lithium hydroxide monohydrate, 2.0g of aluminum oxide, 17.7g of titanium dioxide and 45.0g of ammonium dihydrogen phosphate were mixed with anhydrous ethanol, and 370g of zirconium oxide balls were added. The mixture was ball-milled at 300rpm for 3h, and then dried at 80℃ for 5h and sieved to obtain a uniformly mixed precursor. The above precursor was placed in a corundum crucible, heated to 450℃ at a heating rate of 5℃ / min, kept warm for 2h, and then continued to heat to 950℃ and kept warm for 4h to obtain an intermediate. The above materials were crushed, ball-milled, dried, and sieved to obtain ultrafine lithium titanium aluminum phosphate solid electrolyte materials.

[0068] Comparative Example 2

[0069] 8.18g of lithium hydroxide monohydrate, 2.0g of alumina, 17.7g of titanium dioxide and 45.0g of ammonium dihydrogen phosphate were mixed with anhydrous ethanol, and 370g of zirconium oxide balls were added. The mixture was ball-milled at 300rpm for 3h, and then dried at 80°C for 5h and sieved to obtain a uniformly mixed precursor. The above precursor was placed in a corundum crucible, heated to 450°C at a heating rate of 5°C / min, and then heated to 950°C for 4h after 2h to obtain an intermediate. The above intermediate was crushed, ball-milled, dried, and sieved, and then kept at 10MPa for 10min to obtain a dense intermediate. Subsequently, the temperature was increased to 800°C at a heating rate of 5°C / min and kept for 8h to obtain a lithium aluminum titanium phosphate material. The above materials were crushed, ball-milled, dried, and sieved to obtain an ultrafine lithium aluminum titanium phosphate solid electrolyte material.

[0070] The following is a structural characterization and performance measurement of the materials prepared in the above examples and comparative examples. The specific experimental contents are as follows:

[0071] Figure 1 This is a SEM image of the intermediate of Example 1. It can be seen from the image that the particle size of the material is below 2 μm and the particle size distribution is relatively uniform.

[0072] Figure 2 is a SEM image of fluorine-doped lithium aluminum titanium phosphate in Example 1, and Figure 1 Comparison shows that while the grains grow, lithium aluminum titanium phosphate still maintains a dense structure without pores. This shows that fluorine doping can not only promote grain growth, but also make the material structure more dense.

[0073] Figure 3 is the XRD diagram of fluorine-doped lithium aluminum titanium phosphate in Example 1, compared with Figure 4 In the XRD diagram of lithium aluminum titanium phosphate in comparative example 2, the peak intensity of the LiTiPO5 diffraction peak at 27.5° to 28.5° in Example 1 is significantly lower than that in comparative example 2. This shows that fluorine doping can effectively inhibit the formation of impurity phases and improve the purity of lithium aluminum titanium phosphate materials.

[0074] Figure 5 , Figure 6 The AC impedance diagrams are respectively the fluorine-doped lithium titanium aluminum phosphate in Example 1 and the lithium titanium aluminum phosphate in Comparative Example 2. It can be seen from the figure that the resistance of Example 1 is significantly lower than that of Comparative Example 2. Combined with Table 1, the ionic conductivity of Examples 1, 2, and 5 is higher than that of Comparative Example 2. This shows that doping can effectively improve the ionic conductivity of lithium titanium aluminum phosphate solid electrolyte materials.

[0075] Table 1 Performance of electrolyte blocks of examples and comparative examples

[0076] Serial number <![CDATA[Ionic conductivity (10 -4 S / cm)]]> Particle density Example 1 10.1 94.7% Example 2 8.8 94.3% Example 5 5.9 94.1% Example 6 5.2 95.2% Comparative Example 2 3.5 91.1%

[0077] In addition, it can be seen from Table 1 that the particle density of Examples 1, 2, and 5 is significantly higher than that of Comparative Example 2. This indicates that doping can increase the particle density of the material by making the crystal structure more compact.

[0078] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A doped lithium aluminum titanium phosphate solid electrolyte material, characterized in that: The chemical composition of the doped lithium aluminum titanium phosphate solid electrolyte material is Li 1+z M y Al x Ti 2-x-y P3O 12-b F a ; Among them, 0 ≤ x, y ≤ 0.4, 0 ≤ a, b ≤ 0.8, 0 < z ≤ 0.8, and M is one or more combinations of Zn, Mg, Ca, Sr, Si, and Sn elements.

2. A method for preparing the doped lithium aluminum titanium phosphate solid electrolyte material as claimed in claim 1, characterized in that: Specifically, it includes the following steps: (1) Mix an excessive lithium source with an aluminum source, a titanium source, a phosphorus source, a fluorine source, and a doping element-containing compound weighed according to the stoichiometric ratio described in Claim 1, add a solvent to submerge the raw materials, then perform wet ball milling, and then obtain uniformly mixed raw materials through drying and screening. (2) Pelletize the uniformly mixed raw materials in step (1) to obtain a dense precursor. (3) Calcinate the uniformly mixed raw materials in step (1) or the dense precursor after pelletizing in step (2) to obtain an intermediate. (4) Crush, wet ball mill, dry, and screen the intermediate obtained in step (3) to obtain an intermediate powder. (5) Pelletize the intermediate powder obtained in step (4) to obtain a dense intermediate. (6) Calcinate the intermediate obtained in step (3), the intermediate powder obtained in step (4), or the dense intermediate obtained in step (5) again, and cool it to room temperature to obtain the doped lithium titanium aluminum phosphate solid electrolyte material.

3. The method for preparing the doped lithium aluminum titanium phosphate solid electrolyte material according to claim 2, characterized in that: It also includes: Crush and pulverize the intermediate obtained in step (3) or the doped lithium titanium aluminum phosphate solid electrolyte material obtained in step (6), perform ultra-fine ball milling, then perform drying and screening to obtain an ultra-fine doped lithium titanium aluminum phosphate solid electrolyte material.

4. The method for preparing the doped lithium aluminum titanium phosphate solid electrolyte material according to claim 3, characterized in that: The particle size of the ultra-fine doped lithium titanium aluminum phosphate solid electrolyte material is 0.02 - 2 microns.

5. The method for preparing the doped lithium aluminum titanium phosphate solid electrolyte material according to claim 2, characterized in that: In step (1), the fluorine source is one or more combinations of aluminum fluoride, magnesium fluoride, calcium fluoride, zinc fluoride, tin fluoride, zirconium fluoride, silicon fluoride, and lithium fluoride. The molar ratio of the lithium source is 10% - 20% in excess, and the solvent is one or more combinations of water or alcohol solvents.

6. The method for preparing the doped lithium aluminum titanium phosphate solid electrolyte material according to claim 2, characterized in that: In step (3), the calcination process is: heat up to 400 - 600 °C at a heating rate of 1 - 10 °C / min and hold for 2 - 4 h, then heat up to 800 - 1000 °C at a heating rate of 1 - 5 °C / min, and the holding time is 2 - 12 h.

7. The method for preparing the doped lithium aluminum titanium phosphate solid electrolyte material according to claim 2, characterized in that: In steps (2) and (5), the pelletizing pressure is 5 - 30 MPa, and the pelletizing time is 3 - 30 min.

8. The method for preparing the doped lithium aluminum titanium phosphate solid electrolyte material according to claim 2, characterized in that: In step (6), the temperature of the second calcination is 800 - 1200 °C, and the holding time is 2 - 12 hours.

9. A lithium ion battery, characterized in that: The lithium ion battery includes the doped lithium titanium aluminum phosphate solid electrolyte material described in Claim 1 or the doped lithium titanium aluminum phosphate solid electrolyte material prepared by the method described in any one of Claims 2 - 8.

Citation Information

Patent Citations

  • Preparation method of high-density lithium aluminum titanium phosphate solid electrolyte material

    CN116093421A

  • Retraction Spring for retracting a Brake Pad and Brake Assembly including it

    KR1020210128916A

Cited By

  • Doped titanium-aluminum-lithium phosphate solid-state electrolyte membrane as well as preparation method and application thereof

    CN121726494A

  • Fluorine-doped LATP composite solid electrolyte membrane and preparation method and application thereof

    CN122224922A